PELATIHAN VIDEO EDITING DI SMP IT MADANI - Ahmad Zamsuri; Wenni Syafitri; Febrizal As-Syam (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2018)
SMP IT Madani is formed from LAZ Swadaya Ummah Riau Province. SMP IT Madani is a free school. The vision promoted by SMP IT Madani is as follows: "Becoming a model of educational institutions in empowering the Dhuafa who gave birth to the generation of the independent and outstanding Qur'an." Such a great vision does not make SMP IT Madani undo its steps to gets in the way. SMP IT Madani wants to make an improvisation of activity documentation technique, because so far what has been done is not maximal. Activity documentation is only limited to using official technology, without improvising that has the attraction. Because Middle School Madani has a target to find prospective students who have unique criteria, namely weak economic family but have functional academic abilities, this documentation can be used as a place for school promotion. The implementation of this activity was successful based on data from respondents. Respondents consisted of SMP IT Madani community. The implementation of this activity can be said to be successful, because KR value and KS before and after the implementation of the activity get a positive response, namely Value 1. This activity was successfully implemented and by the expected result.